Using primary health care (PHC) workers and key informants for community based detection of blindness in children in Southern Malawi - Kalua Khumbo; Ng'ongola Ruby; Mbewe Frank; Gilbert Clare (BMC, 2012)
Abstract Background There is great interest in providing primary eye care (PEC) through integration into primary health care (PHC). However, there is little evidence of the productivity of PHC workers in offering primary eye care after training and integration, and there is need to compare their effectiveness to alternative methods. The current study compared the effectiveness of trained Health Surveillance Assistants (HSAs) versus trained volunteer Key Informants (KIs) in identifying blind children in southern Malawi. Methods A cluster community based study was conducted in Mulanje district, population 435 753. Six clusters each with a population of approximately 70 000 to 80 000, 42% of whom were children were identified and randomly allocated to either HSA or KI training. From each cluster 20 HSAs or 20 KIs were selected for training. Training emphasized the causes of blindness in children and their management, and how to identify and list children suspected of being blind. HSAs and KIs used multiple methods (door to door, school screening, health education talks, village announcements, etc.) to identify children. Using the World Health Organization (WHO) estimates (eight blind children per 10 000 children); approximately 144 to 162 blind children were expected in the chosen clusters. Listed children were brought to a centre within the community where they were examined by an ophthalmologist and findings recorded using the WHO form for examining blindness in children. Results A total of 59 HSAs and 64 KIs were trained. HSAs identified five children of whom two were confirmed as blind (one blind child per 29.5 HSAs trained). On the other hand, the KIs identified a total of 158 children of whom 20 were confirmed blind (one blind child per 3.2 KIs trained). More blind boys than girls were identified (77.3% versus 22.7%) respectively. Conclusion Key Informants were much better at identifying blind children than HSAs, even though both groups identified far fewer blind children compared with WHO estimates. HSAs reported lack of time as a major constraint in identifying blind children. Based on these findings using HSAs for identifying blind children would not be successful in Malawi. Gender differences need to be addressed in all childhood blindness programs to counteract the imbalance.